Thermally Reduced Soft Magnetic Cufe Nanoparticles for High Performance Electrical Devices - Casagrande-Denardin, J (Institute of Electrical and Electronics Engineers Inc., 2021)
Developing economically soft magnetic materials for high-performance electrical devices is indispensable. Here, we present the structural and magnetic properties of thermally reduced soft CuFe nanoparticles. The fcc cubic structure of iron-rich Cu37Fe63 and their composition was confirmed by Rietveld refinement. Cu37Fe63 nanoparticles exhibited high saturation magnetization and coercivity of 127 eμg (142 eμg) and 4.3 Oe (31 Oe), respectively, at 300 K (5 K). They showed transitions at ∼ 34 and ∼ 249 K due to the Kondo temperature of CuFe and minor fraction of CuFe2O4, respectively. The exchange coupling between Cu and Fe was not significant, as demonstrated by field-cooled magnetization curves at 5 K. The magnetocaloric effect (MCE) in the range of fields and temperatures was estimated whereas the maximum MCE of -8.71× 10-2 J.kg-1. K-1 was achieved at 222 K. These soft magnetic materials, which exhibited stable high saturation magnetization with less heating effect during magnetization and demagnetization cycles, would be suitable candidates for magnetic applications. © 1965-2012 IEEE.